Prévalence de l’antibiorésistance au cours de l’infection urinaire : étude rétrospective au laboratoire de l’hôpital Lotfi - MEDJDEN REGUIA MAJDA; LAGGOUN SIRINE (université ammar telidji laghouat, 2024)
ABSTRACT : Background: Urinary tract infections (UTIs) have become a major public health challenge due to the increasing resistance of bacteria to antibiotics. This study aims to investigate this issue, highlighting its concerning impact on treatments and public health. It underscores the urgency for prompt and concerted action, promoting rational antibiotic use, intensifying research, and raising public awareness to safeguard the health of future generations. Materials and Methods: This retrospective observational study was conducted at the microbiology laboratory of Colonel LotfiAkid Hospital in Laghouat over a two-year period from January 1, 2022, to December 30, 2023. It examined antibiotic resistance in urinary tract infections (UTIs) by analyzing the antibiograms of hospitalized patients, outpatients, and emergency department patients. Results: UTIs were predominantly caused by enterobacteria, mainly Escherichia coli followed by Klebsiella pneumoniae and Proteus mirabilis, with a small proportion of Gram-positive bacteria. Enterobacteria exhibited high resistance to several commonly used antibiotics, including ampicillin, amoxicillin, amoxicillin-clavulanic acid, ofloxacin, and cefazolin, with lower resistance to Fosfomycin. Conclusion: The rise in antibiotic resistance poses a threat to public health, necessitating a comprehensive approach that combines individual prevention and effective public health policies to avert dire consequences.
cd-rom